Розвиток друкованих ЗМІ в країнах з перехідною економікою: досвід Польщі і Болгарії - Бондарева, А. Ф.; Bondareva, А. (My University, 2010)
This article considers an experience of mass media dissociating from the state in the east Europe countries of former socialistic bloc. The experience of inculcation of multinational corporations into mass media market of Poland Republic and Bulgaria Republic at the period of this countries transitioning from planned economy to the market one was considered. This experience can be used through forming of Ukrainian public policy concerning mass media.
Бондарева А. Ф. Розвиток друкованих ЗМІ в країнах з перехідною економікою: досвід Польщі і Болгарії / А. Ф. Бондарева // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 317-325.
Keywords: друковані ЗМІ в Польщі і Болгарії; державна політика в сфері ЗМІ; засоби масової інформації Польщі та Болгарії; средства масовой информации Польши и Болгарии; государственная политика в сфере СМИ; печатные СМИ в Польше и Болгарии